Kloning Gen Penyandi Antigen HBsAg100 dalam Rangka Produksi Protein Rekombinan Sebagai Model Imunogen untuk Menghasilkan Antibodi - S. Riyadi; R. RA Maheswari; M. Sudarwanto; Fransiska RZ; M. Ali (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2011)
Since one decade ago, a new paradigm of vaccine design is emerging. Instead of attenuated virulent microorganisms or killed virulent microorganisms, effective subunit vaccines were developed using recombinant DNA technology. By using the technology, selected genes of the virulent microorganisms can be cloned, expressed, and evaluated as vaccine components. In this research, hydrophilic domain of S protein (aa 100-164)-encoding gene of hepatitis B surface antigen was cloned for vaccine candidate production. The gene was ligated with pGEX-4T-2 vector and sequenced. Sequences aligment of the amplified fragment with genome of hepatitis B virus indicated that the sequences were identical. A major result achieved from this research was clones carrying S antigens-encoding gene that could be used further for production of recombinant hepatitis B vaccine candidates.